Richter's transformation in patients with chronic lymphocytic leukaemia: a Nationwide Epidemiological Study. Issue 6 (11th May 2020) - Ben-Dali, Yasmin; Hleuhel, Mariam H.; da Cunha-Bang, Caspar; Brieghel, Christian; Poulsen, Christian B.; Clasen-Linde, Erik; Bentzen, Hans H. N.; Frederiksen, Henrik; Christiansen, Ilse; Nielsen, Linda H.; Enggaard, Lisbeth; Helleberg, Marie; et al.
Abstract: Richter's transformation (RT) refers to the development of an aggressive lymphoma in patients with chronic lymphocytic leukemia (CLL). Approximately, 2–10% of patients with CLL develop RT, most often as diffuse large B-cell lymphoma. To assess the incidence of RT, we examined risk factors for RT and death among patients with RT in a nationwide CLL cohort (from 2008 to 2016). Among 3772 patients, 113 had biopsy-proven RT. With a median follow-up of 4.3 years, the 5-year cumulative incidence of RT was 2.8%. Advanced Binet stage (B/C) ( p <.001), unmutated IGHV ( p <.001), and del(17p) ( p <.001) were independently associated with risk of developing RT. Half of the patients with RT (49%) were treatment-naïve prior to transformation and demonstrated longer survival after RT compared to patients previously treated for CLL (6.1 vs. 2.8 years, p =.03). Whether this finding could be explained by a higher proportion of clonally unrelated RT among treatment-naïve patients, remain to be addressed.